2016
DOI: 10.5505/phd.2016.96967
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Presence: A Theoretical Overview

Abstract: Throughout history, the concept of presence has been discussed in the fields of psychology, philosophy, and spirituality. It was first introduced to the nursing field in the mid-1960s, and discussion has continued into the present day. Different definitions and classifications have been made from the different points of views. Concept of presence has been defined per following. According to well-known writers in nursing area, there are a numbers of different definitions for the concept of presence. For instanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
0
13
0
3
Order By: Relevance
“…Sources have also indicated that when psychiatric nurses recognize values and beliefs in their patients, they are better able to help patients work through potential negative values they may associate with their illness (Huguelet et al, 2010; Menezes & Moreira-Almeida, 2010). When nurses assist patients in understanding how their values are important to their particular experiences, patients understand themselves better and are empowered to make responsible decisions regarding their health (Yesilot & Oz, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Sources have also indicated that when psychiatric nurses recognize values and beliefs in their patients, they are better able to help patients work through potential negative values they may associate with their illness (Huguelet et al, 2010; Menezes & Moreira-Almeida, 2010). When nurses assist patients in understanding how their values are important to their particular experiences, patients understand themselves better and are empowered to make responsible decisions regarding their health (Yesilot & Oz, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Isso significa reconhecer e indagar as respostas únicas e humanas dos utentes ao sofrimento, e não apenas perguntar sobre a apresentação de problemas e necessidades (1,35) . Para "Conseguir ver" os utentes o enfermeiro deve ser curioso e respeitador, fazer perguntas, demonstrando preocupação genuína pela experiência do utente (34,47) ; Ouvir atentamente as narrativas da experiência e observar preocupações especiais subjacentes (40,46,48) ; Observar atentamente as reações e comportamentos (41,42,49,50) ; Observar com sensibilidade sentimentos, tanto os expressos quanto os experimentados por si mesmo (44,49,50) ; Considerar cuidadosamente o uso de palavras e tempo na criação de relações terapêuticas apropriadas (13,50) .…”
Section: Atributos Que Garantem a Qualidade Da Presençaunclassified
“…Ações específicas utilizadas na Presença incluem o uso de terapêutico e afetuoso do toque, silêncio atento, oportuno e terapêutico, escuta verdadeira, contato visual, sorriso, sentido de humor, positivo e congruente, postura corporal positiva e partilha de narrativas (3,26,46,47,48,49) .…”
Section: Atributos Que Garantem a Qualidade Da Presençaunclassified
“…As nursing is a profession based on human relations, nurses are required to establish an interaction with individuals of all ages and socioeconomic classes. 1 By considering these interactions, in her psychodynamic nursing theory, Peplau 2 defined nursing as the "therapeutic interpersonal process" and stated that interpersonal relationships are crucial in nursing. In the theory of interaction, Orlando, 3 who was influenced by Peplau's studies, also drew attention to the mutual relationship between patient and nurse, and remarked that nursing is formed by the "dynamic nurse-patient relationship."…”
Section: Introductionmentioning
confidence: 99%